Volumineux Mélanome Malin De La Conjonctive Multi Récidivant À Propos d’un Cas - H. Y, Abba Kaka.; M H, Ali.; M, Boubacar.; F, Moussa.; A, Amza. (European Scientific Journal, ESJ, 2016)
Melanoma of the conjunctiva is a tumor that develops from the conjunctival melenocytes. It often reoccurs even after several surgical removals. The authors present the case of a 45 years old woman who was at first seen in our outpatient clinic with a spitz naevus of the conjunctiva of the right eye since more than 20 years ago. This naevus which was excised twice and then the eye enucleated underwent malignant transformation into a voluminous multi-recidivant malignant melanoma weighing after surgical removal 350g and measures 6x12x5cm.